2018
DOI: 10.1080/1478422x.2017.1393245
|View full text |Cite
|
Sign up to set email alerts
|

The study for direct SCC fabrication in STS 304 pipe

Abstract: Stress corrosion cracking is one of the aging phenomena for the major structure components in nuclear power plant. During the operation of a power plant, stress corrosion cracks are initiated and grown especially in dissimilar weldment of primary loop components. Among the three factors (susceptible material, residual stress, and corrosive environment) which make the SCC, the residual stress becomes a critical factor for stress corrosion crack when it is difficult to improve the material of the components and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…More detailed characterization of the DWMJ mechanical properties will greatly help the research of the crack tip mechanical field. In addition to the mechanical heterogeneity, the residual stress of the DMWJ also has a significant influence on the mechanical field of the crack tip, and it is the dominant driving force affecting SCC behaviors [18][19][20][21]. Some scholars found that the residual stress will noticeably change the stress and plastic strain of the crack tip, and the residual stress is redistributed on account of the crack propagation, which results in the mechanical field of the crack tip becoming more complex [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…More detailed characterization of the DWMJ mechanical properties will greatly help the research of the crack tip mechanical field. In addition to the mechanical heterogeneity, the residual stress of the DMWJ also has a significant influence on the mechanical field of the crack tip, and it is the dominant driving force affecting SCC behaviors [18][19][20][21]. Some scholars found that the residual stress will noticeably change the stress and plastic strain of the crack tip, and the residual stress is redistributed on account of the crack propagation, which results in the mechanical field of the crack tip becoming more complex [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the stochastic fluctuations of biological assemblies such as chromosomes [10], the cytoskeleton [2,[11][12][13][14], and cellular membranes [15][16][17]. Indeed, while these fluctuations can at first sight appear indistinguishable from thermal Brownian motion, they are in many cases driven by energy-consuming processes at molecular scales [1,2,8,9,18,19]. This molecular scale activity can propagate to mesoscopic scales, giving rise to non-equilibrium dynamics that breaks detailed balance [9,[20][21][22][23][24][25] or that violates the fluctuation dissipation theorem [12,15,16,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%